Apical root resorption during intrusion and extrusion of upper incisors - (:unkn) unknown (My University, 2009)
Amaç: İntrüzyon ve ekstrüzyon sırasındaki üst santral keserlerdeki apikal kök rezorpsiyonunun insidans ve derecesinin belirlenmesi ve ortodontik tedavi sonrasındaki minimal üst santral keser hareketine sahip kontrol grubu ile kök kısalma miktarının karşılaştırıl-masıdır. Bireyler ve Yöntemler: Araştırmaya, üst keserlerde intrüzyon ya da ekstrüzyon ihtiyacı olan 38 hasta seçilmiştir. Vertikal yönde üst keser değişikliği olmayan 20 hasta, kontrol grubu olarak dahil edilmiştir. Yaş ortancaları, intrüzyon, ekstrüzyon ve kontrol grupları için sırasıyla 17,3, 15 ve 12,7 yıldır. SNA, SNB, ANB, FMA, IMPA açıları, overjet, overbite, üst santral keserin palatal düzleme göre inklinasyonu, keser ucu ve apeksinden PTV düzlemine olan ve üst santral keserin rezistans merkezinden palatal düzleme olan dik mesafeler ölçüldü. Her hasta için apikal kök rezorpsiyonunun miktarı, başlangıç kök boyu, final kök boyundan çıkartılarak belirlendi. Bulgular: Tüm gruplarda tedavi sonrasında kök kısalması bulundu. Ortanca kök rezorpsiyon miktarı; intrüzyon, ekstrüzyon ve kontrol grupları için sırasıyla; 0,9, 1,2 ve 0,6 mm idi.Sonuç: Kök rezorpsiyon miktarı, üst santral keserlerin vertikal apikal hareket miktarıyla ilişkili değildi.

Aim: To determine the incidence and degree of apical root resorption of the upper central incisors during intrusion and extrusion and to compare the amount of root shortening with a control group having minimal upper central incisor movement after orthodontic treatment. Subject and Methods: Thirty-eight patients were selected on the basis of intrusion or extrusion needs of the upper incisors. Twenty patients who had no vertical upper incisor change were included as control group. The median ages of the subjects were 17.3, 15 and 12.7 years for the intrusion, extrusion and control groups respectively. SNA, SNB, ANB, FMA, IMPA angles, overjet, overbite, inclination of the upper central incisor to the palatal plane, the perpendicular distances from the incisor tip and apex to the PTV plane and from the centre of resistance of the upper central incisor to palatal plane were measured on the cephalograms. Results: The amount of apical root resorption was . determined for each patient by subtracting the initial tooth length from the final tooth length. Root shortening following orthodontic treatment was found in all groups. The median apical root resorption was 0.9, 1.2 and 0.6 mm in the intrusion, extrusion and control patients respectively.Conclusion: The extent of root resorption was not related to the amount of vertical apical movement of the upper central incisors.
Üst keserlerin intrüzyonu ve ekstrüzyonu sırasında oluşan apikal kök rezorbsiyonu
Keywords: Diş Hekimliği